Smellscape perceptions in hospital waiting areas: influential factors and semantic dimensions - Chong Gao; Shanshan Zhang; Xiaolong Zhao (Taylor & Francis Group, 2024)
Smell can have significant physical and psychological impacts on space users, especially in hospital waiting areas where smells are complex, and users are vulnerable. Understanding how smellscapes affect patients and their companions may help improve space users' interactions with such environments. This study aimed to identify odour types in hospital waiting areas, their influential factors, impacts on odour perception, and key aspects to characterise and evaluate the smellscape in typical waiting areas. An internet survey and field investigations were conducted in China, and subsequent data were analysed. Results showed that 1) nine primary odours were identified in hospital waiting areas, 2) people have negative but relatively tolerant attitudes towards the odours, 3) several demographic and environmental factors impact people's odour perception and evaluation, 4) the evaluation of smellscapes is influenced by the overall environmental judgement, with better odour experience reported in smaller and relatively closed waiting areas, and 5) three dimensions - health, emotion, and quality - were identified to characterise the smellscape. This study highlights the importance of smellscape design and management in healthcare environments, considering odour types, individual differences, spatial features, and other senses to systematically improve the smellscape.